PENERAPAN ARSITEKTUR KONTEMPORER PADA PERANCANGAN OFFICE PARK DI KAWASAN SOUTHCITY, TANGERANG SELATAN - Rafly Saputra; Harfa Iskandaria; Putri Suryandari (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
How to design an Office Park that is able to accommodate all comfortable office activities taking into account the need for office support facilities. Purpose The design object as an office is specifically intended to accommodate activities related to the implementation of administrative, management, commerce, and economic work. However, design objects include activities related to support facilities within them. The first step in writing this article was to collect factual data as a background for choosing a topic, then obtain field data such as location, situation, and users. Two methods were used to collect this data, namely: Primary Data and Secondary Data. In designing this building applying the concept of contemporary architecture because this concept of contemporary architecture is very suitable and in accordance with the office park area because contemporary architecture is not limited by a certain era so the facade that is created will be more flexible. Office Park is an area consisting of several rental offices which will be the preference of corporate actors to rent offices for work.